A novel power flow control transformer for transmission grids and its steady-state analysis - Yang Peng; Xiang Chenmeng; Tian Yuan; Gao Shuguo; Dai Lujian; Du Wei (Science and Technology for Energy Transition)
New energy sources such as solar and wind power are increasingly being integrated into the power system. Due to their inherent randomness, volatility, and intermittency, these renewable energy sources pose significant challenges to power flow control, particularly in transmission grids. This paper presents a novel topology of power flow control transformers for high-voltage transmission grids, aiming to address the insufficient reactive power regulation capability of traditional Phase-Shifting Transformers (PST). To thoroughly investigate the voltage and power flow regulation characteristics of the proposed topology, a steady-state port circuit model is initially developed. Given the complexity of the port circuit model and its inability to intuitively represent the voltage conversion relationship, a steady-state simplified equivalent model is subsequently developed. Through comprehensive simulation analysis and experimental validation, the feasibility of the proposed topology and the accuracy of the models are confirmed. The research findings indicate that this topology can significantly broaden the reactive power regulation range, thereby enabling the four-quadrant operation of the power flow working point. The simplified equivalent model accurately captures its voltage regulation and phase-shifting characteristics, demonstrating robust engineering applicability. Furthermore, the phase compensation voltage exerts a significant influence on active power regulation, while the amplitude compensation voltage has a pronounced effect on reactive power regulation.